2007
DOI: 10.1037/0893-164x.21.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extinction context and retrieval cues on renewal of alcohol-cue reactivity among alcohol-dependent outpatients.

Abstract: Pavlovian conditioning models have led to cue-exposure treatments for drug abuse. However, conditioned responding to drug stimuli can return (be renewed) following treatment. Animal research and a previous study of social drinkers indicated that extinction is highly context dependent but that renewal could be reduced by the inclusion of a cue from the extinction context. This study extends this research to a clinical sample. Alcohol-dependent outpatients (N = 143) completed an extinction trial to reduce cravin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…Cue exposure therapy-that is, extinction of the CS through repeated nonreinforced presentations-has been frequently attempted, but a metaanalysis of a substantial literature has indicated that overall it results in little benefit (Myers & Carlezon 2012), in part because of the contextual specificity of extinction learning (Conklin & Tiffany 2002); however, the view is perhaps less pessimistic for alcoholics (Glautier et al 1994, MacKillop & Lisman 2008, Stasiewicz et al 2007). Attempts to enhance drug CS extinction with the glutamate receptor agonist D-cycloserine, following demonstrations of enhanced Pavlovian fear extinction (Davis 2002, Lee et al 2006b), have also generally been unsuccessful (Myers & Carlezon 2012) and may even result in an increase, not a decrease, in craving elicited by later exposure to the CS (Price et al 2013), an explanation for which is discussed below.…”
Section: Prospects For New Treatments Of Addictionmentioning
confidence: 98%
“…Cue exposure therapy-that is, extinction of the CS through repeated nonreinforced presentations-has been frequently attempted, but a metaanalysis of a substantial literature has indicated that overall it results in little benefit (Myers & Carlezon 2012), in part because of the contextual specificity of extinction learning (Conklin & Tiffany 2002); however, the view is perhaps less pessimistic for alcoholics (Glautier et al 1994, MacKillop & Lisman 2008, Stasiewicz et al 2007). Attempts to enhance drug CS extinction with the glutamate receptor agonist D-cycloserine, following demonstrations of enhanced Pavlovian fear extinction (Davis 2002, Lee et al 2006b), have also generally been unsuccessful (Myers & Carlezon 2012) and may even result in an increase, not a decrease, in craving elicited by later exposure to the CS (Price et al 2013), an explanation for which is discussed below.…”
Section: Prospects For New Treatments Of Addictionmentioning
confidence: 98%
“…Among the clinical efficacy trials reviewed, at least one [21] attempted to address the issue of renewal by having participants practice CET procedures at home as part of a homework assignment, though individuals in the CET group did not fare better than the comparison control group with respects to clinical outcome. Taken together, while later studies failed to replicate earlier positive findings regarding renewal effects [18,19], or failed to find enhanced efficacy of CET when taking renewal into account [21], the body of research in this area remains small. Thus, there is arguably enough positive evidence to merit further systematic investigation of this phenomenon.…”
Section: Recent Efficacy Trialsmentioning
confidence: 48%
“…In an attempt to replicate and extend the findings of Brandon and Collins, Staciewicz, and colleagues [18] also tested whether conducting cue exposure trials in a novel context would result in renewal and whether an extinction reminder would moderate this finding. In addition, however, these investigators assessed whether the extinction reminder would be more effective if the saliency of the extinction reminder was increased.…”
Section: Studies Investigating the "Renewal" Effectmentioning
confidence: 92%
“…During Study 1 and Study 2, we will test 4 concepts related to Pavlovian extinction literature that are salient to human food intake: 1) number of extinction trials, 2) single vs. multiple foods in exposures, 3) extinction training in multiple contexts and 4) the use of an enhanced partial reinforcement schedule. (See Figure 1 ) All of the trials will incorporate extinction cues 2223 (bracelets) to remind the children of their new learning and thus help to bridge extinction between contexts. Following an exposure learning session, the children will verbalize what they have learned as a result of the session to enhance inhibitory processes.…”
Section: Methodsmentioning
confidence: 99%
“…132021 Furthermore, extinction may be bridged across two or more contexts by increasing the number of contexts in which extinction occurs 16 and the use of extinction cues. 2223 …”
Section: Introductionmentioning
confidence: 99%